The sensory system of the esophagus––what do we know?. Issue 1 (6th September 2016) - Brock, Christina; Gregersen, Hans; Gyawali, C. Prakash; Lottrup, Christian; Furnari, Manuele; Savarino, Edoardo; Novais, Luis; Frøkjær, Jens Brøndum; Bor, Serhat; Drewes, Asbjørn Mohr
Abstract : The nervous innervation and complex mechanical function of the esophagus make sensory evaluation difficult. However, during the last decades, several new techniques have made it possible to gain insight into pain processing of nociceptive signals. The current review highlights the sensory innervation and possibilities for quantitative sensory testing, the mechanosensory properties, the potential of high‐resolution manometry and imaging, and the sensory system in special conditions, such as Barrett's esophagus. It is mandatory to understand the complex pathophysiology of the esophagus to enhance our understanding of esophageal disorders, but it also increases the complexity of future experimental and clinical studies. The new methods, as outlined in the current review, provide the possibility for researchers to enhance the quality of interdisciplinary research and to gain more knowledge about sensory symptoms and treatment possibilities.